Chemical and isotopic compositions of rocks and minerals from the Franz Josef Land Archipelago - L K Levsky; N M Stolbov; E S Bogomolov; I M Vasil extquotesingleeva; E M Makar extquotesingleeva (PANGAEA, 2006)
Rb, Sr, Sm, Nd, U, and Pb contents and Sr, Nd, and Pb isotopic composition were determined in tholeiite and subalkaline basalts (in both whole-rock samples and individual minerals) from the Franz Josef Land Archipelago. Isotopic data obtained for the Arctic basin are similar to those for islands from the Pacific, Atlantic, and Indian oceans. The assimilation of crustal (sedimentary) rocks by primary depleted material makes isochron determination of basalt age difficult or impossible. The subalkaline basalts (basaltic andesites) were presumably formed by the metasomatic introduction of incompatible elements in tholeiitie basalts and, only partially, through crustal contamination and fractional crystallization.